A influência da cultura familiar no cuidado à criança vítima de queimadura - Brito, Maria Eliane Maciel de (2009)
The knowledge about the cultural and familiar view of accidents with burns in children allow to contribute the creation of strategies that value not only the cure of the sickness, yet conditions of prevention of new accidents with children, but also to promote conditions of dialogue between family and health professionals essential to humanization in Burn Specialized Centers. This study had as objective to understand as the beliefs, values and style of life of the families influence in the care of children victims of burns intern in a Burnt Treatment Center, in Fortaleza, Ceará; and characterize families of burnt children intern from April to August of 2008. It is an ethnographic approach accomplish in a Hospital Institution of Urgency and Emergency, where there is a Burnt Treatment Center in the city of Fortaleza-Ceará from April to August of 2008, which has as key informers the families of burnt children. The whole collect and analysis process was based in ethnonursery proposed by Leininger (1991), to gather the data were made use of Observation-Participation-Reflection pattern (O.P.R.). In the data arrangement and analysis the Ethnonursery was the guide in the following stages: gathering information and documents; to cluster the storage data in the field day book; contextual or standard analysis and identification of main themes, discovery of research, theoretical formulations and warnings. From the ethnographic analysis sprout three cultural rules: 1) The child is very naughty, the families aim the curiosity of the children as the cause of the accident with burns, not knowing the stages of growing and development of the children, blame the infant for the burn. 2) She washed with water and brought to the hospital, the families think that to wash the burn with water is a way to render pleasant the pain of the burn and to forward the child to a hospital, to establish a way to offer a right care after the accident; 3) to watch more out for, it shows the significance to prevent other accidents with burns and to drive away children of the danger, as to take them away of the kitchen. It was perceived that mothers in spite of having their cultural knowledge, they learn a lot during the study, for as they have much uncertainty that day by day was enlightened and made them think about their behavior with their children. Therefore, we conclude that is essential the cultural approach of the professional to take care of children victims of burns and the Health Education must be available as strategies of welcome that consent the family and the child can feel safe